Solve for x
x=\frac{\sqrt{17}-1}{4}\approx 0.780776406
x=\frac{-\sqrt{17}-1}{4}\approx -1.280776406
Graph
Share
Copied to clipboard
-6x^{2}-3x+6=0
All equations of the form ax^{2}+bx+c=0 can be solved using the quadratic formula: \frac{-b±\sqrt{b^{2}-4ac}}{2a}. The quadratic formula gives two solutions, one when ± is addition and one when it is subtraction.
x=\frac{-\left(-3\right)±\sqrt{\left(-3\right)^{2}-4\left(-6\right)\times 6}}{2\left(-6\right)}
This equation is in standard form: ax^{2}+bx+c=0. Substitute -6 for a, -3 for b, and 6 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-\left(-3\right)±\sqrt{9-4\left(-6\right)\times 6}}{2\left(-6\right)}
Square -3.
x=\frac{-\left(-3\right)±\sqrt{9+24\times 6}}{2\left(-6\right)}
Multiply -4 times -6.
x=\frac{-\left(-3\right)±\sqrt{9+144}}{2\left(-6\right)}
Multiply 24 times 6.
x=\frac{-\left(-3\right)±\sqrt{153}}{2\left(-6\right)}
Add 9 to 144.
x=\frac{-\left(-3\right)±3\sqrt{17}}{2\left(-6\right)}
Take the square root of 153.
x=\frac{3±3\sqrt{17}}{2\left(-6\right)}
The opposite of -3 is 3.
x=\frac{3±3\sqrt{17}}{-12}
Multiply 2 times -6.
x=\frac{3\sqrt{17}+3}{-12}
Now solve the equation x=\frac{3±3\sqrt{17}}{-12} when ± is plus. Add 3 to 3\sqrt{17}.
x=\frac{-\sqrt{17}-1}{4}
Divide 3+3\sqrt{17} by -12.
x=\frac{3-3\sqrt{17}}{-12}
Now solve the equation x=\frac{3±3\sqrt{17}}{-12} when ± is minus. Subtract 3\sqrt{17} from 3.
x=\frac{\sqrt{17}-1}{4}
Divide 3-3\sqrt{17} by -12.
x=\frac{-\sqrt{17}-1}{4} x=\frac{\sqrt{17}-1}{4}
The equation is now solved.
-6x^{2}-3x+6=0
Quadratic equations such as this one can be solved by completing the square. In order to complete the square, the equation must first be in the form x^{2}+bx=c.
-6x^{2}-3x+6-6=-6
Subtract 6 from both sides of the equation.
-6x^{2}-3x=-6
Subtracting 6 from itself leaves 0.
\frac{-6x^{2}-3x}{-6}=-\frac{6}{-6}
Divide both sides by -6.
x^{2}+\left(-\frac{3}{-6}\right)x=-\frac{6}{-6}
Dividing by -6 undoes the multiplication by -6.
x^{2}+\frac{1}{2}x=-\frac{6}{-6}
Reduce the fraction \frac{-3}{-6} to lowest terms by extracting and canceling out 3.
x^{2}+\frac{1}{2}x=1
Divide -6 by -6.
x^{2}+\frac{1}{2}x+\left(\frac{1}{4}\right)^{2}=1+\left(\frac{1}{4}\right)^{2}
Divide \frac{1}{2}, the coefficient of the x term, by 2 to get \frac{1}{4}. Then add the square of \frac{1}{4} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{1}{2}x+\frac{1}{16}=1+\frac{1}{16}
Square \frac{1}{4} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{1}{2}x+\frac{1}{16}=\frac{17}{16}
Add 1 to \frac{1}{16}.
\left(x+\frac{1}{4}\right)^{2}=\frac{17}{16}
Factor x^{2}+\frac{1}{2}x+\frac{1}{16}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{1}{4}\right)^{2}}=\sqrt{\frac{17}{16}}
Take the square root of both sides of the equation.
x+\frac{1}{4}=\frac{\sqrt{17}}{4} x+\frac{1}{4}=-\frac{\sqrt{17}}{4}
Simplify.
x=\frac{\sqrt{17}-1}{4} x=\frac{-\sqrt{17}-1}{4}
Subtract \frac{1}{4} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}